Floral nectar of the obligate outcrossing Canavalia gladiata (Jacq.) DC. (Fabaceae) contains only one predominant protein, a class III acidic chitinase. (26th June 2017) - Ma, X. L.; Milne, R. I.; Zhou, H. X.; Fang, J. Y.; Zha, H. G.
Abstract: Floral nectar can affect the fitness of insect‐pollinated plants, through both attraction and manipulation of pollinators. Self‐incompatible insect‐pollinated plants receive more insect visits than their self‐compatible relatives, and the nectar of such species might face increased risk of infestation by pathogens carried by pollinators than self‐compatible plants. Proteins in nectar (nectarins) play an important role in protecting the nectar, but little is known regarding nectarins in self‐incompatible species. The nectarins from a self‐incompatible and insect‐pollinated leguminous crop, Canavalia gladiata, were separated using two‐dimensional electrophoresis and analysed using mass spectrometry. The predominant nectarin gene was cloned and the gene expression pattern investigated using quantitative real‐time PCR. Chitinolytic activity in the nectar was tested with different substrates. The C. gladiata nectar proteome only has one predominant nectarin, an acidic class III chitinase (CaChi3). The full‐length CaChi3 gene was cloned, coding for a protein of 298 amino acids with a predicted signal peptide. CaChi3 is very similar to members of the class III chitinase family, whose evolution is dominated by purifying selection. CaChi3 was expressed in both nectary and leaves. CaChi3 has thermostable chitinolytic activity according to glycol‐chitin zymography or a fluorogenic substratem but has no lysozyme activity. Chitinase might be a critical protein component in nectar. The extremely simple nectar proteome in C. gladiata disproves the hypothesis that self‐incompatible species always have more complex nectar proteomes. Accessibility of nectar might be a significant determinant of the evolutionary pressure to develop nectar defence mechanisms.